(untitled) (Medico Legal Update, 2020)
Objective(s): To evaluate university students’ self-management and academic achievement; to compare between these students relative to their self-management and academic achievement; and to determine the relationships between these students’ self-management, academic achievement and their socio-demographic characteristics in the University of Baghdad. For the period of November 2nd 2018 to May 30th 2019. Methods: A descriptive design, using the evaluation and comparison approaches, is employed throughout the study. Two self-evaluation questionnaires are constructed for the purpose of the presents study. Content validity and internal consistency reliability are determined for the study instruments through a pilot study. A non-probability, purposive sample, of (80) university students is selected from the Medical Colleges, College of Engineering, College of Sciences and College of Education in the University of Baghdad. Data are collected through the use of the study instruments and the structured interview technique as means for data collection for the period of February 21st 2019 to March 20th 2019. Data are analyzed through the application of the descriptive statistical data analysis approach which includes frequency, percentage, mean, total score and range and inferential statistical data analysis approach of Analysis of Variance and Multiple Linear Regression. Results: The study depicts that most of the college students experience fair to good level of self-management and good level of academic achievement. Conclusion: The study concludes that students do not present differences in their self-management and academic achievement. Self-management is affected by students’ gender and education and academic achievement is influenced by students’ socioeconomic status